Effectiveness of Increasing Vocabulary and Constructing Sentences for High Class 4/5/6 SDLB for the Deaf Using the MMR Method with Video Media at SLB Riverkids and SLB Putra Jaya - Rhespati, Dian Ayu; Efendi, Mohammad; Hastuti, Wiwik Dwi; Ediyanto, Ediyanto (Jurnal Multidisiplin Madani, 2023)
Deafness is a condition where a child experiences problems with his ability to hear. Deaf children have a small vocabulary. The small vocabulary is caused by poor listening skills so that children are unable to accept new vocabulary which results in difficulties in communicating. Apart from difficulties in communication, they also have difficulty in constructing sentences. One step that can overcome the above problem is to apply the Maternal Reflective Method (MMR). The Reflective Maternal Method (MMR) emphasizes the mother's way of teaching language to children, where the teaching is carried out scientifically. The aim of this research is to analyze MMR on the ability of deaf children in adding vocabulary and constructing sentences. This type of research is Quasi Experimental research with a one group pretest posttest design, which applies five pretests and five posttests. Analysis technique for testing hypotheses using the SPSS 25 for Windows program.The research results showed a significant difference between the pretest results and the posttest results. This is proven by the output results obtained p is 0.000, which means p<0.05 then H0 is rejected and Ha is accepted. This means that there is a significant increase in the vocabulary and sentence learning outcomes of deaf students.The conclusion of this research is that the Maternal Reflective Method (MMR) can influence the addition of vocabulary and sentence construction in deaf children